Hypermethylation of the FOXP3 gene regulates Tregs immunodysregulation in chronic idiopathic thrombocytopenic purpura - Wang, Zengsheng; Lang, Tao; Li, Yan; Zhang, Xiaoyan; Abdur, Muhubair; Mao, Min (Allergologia et Immunopathologia, 2024)
Background: Chronic idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease characterized by a breakdown of immune tolerance; in ITP, the body’s immune system mistakenly attacks and destroys platelets. This study aims to investigate the role and underlying mechanisms of FOXP3 in chronic ITP.Methods: Flow cytometry was used to detect the proportion of CD4+CD25+FOXP3+ regulatory T cells (Tregs) in CD4+CD25+ T lymphocytes from 20 patients with chronic ITP (CITP), 20 acute ITP (AITP) controls, and 20 healthy individuals.CD4+CD25+ Treg cells were isolated from peripheral blood of patients with CITP using magnetic beads and then treated with phosphate-buffered saline solution or decitabine (a methylation inhibitor) for 48 h. The levels of interleukin-2 (IL-2), IL-10, and transforming growth factor-beta1 (TGF-β1) in the plasma and CD4+CD25+ Treg cells were assessed by Enzyme-linked-immunosorbent serologic assay and quantitative real-time polymerase chain reaction (qRT-PCR). FOXP3 level was measured by qRT-PCR and Western blot analysis. Methylation-specific PCR (MS-PCR) was adopted to detect the status of FOXP3 methylation.Results: The number of Treg cells and the contents of IL-2, IL-10, and TGF-β1 decreased in patients with CITP, compared to the AITP control group and normal group. FOXP3 expression was reduced and FOXP3 methylation increased in patients with CITP, compared to the AITP control group and normal group. Hypermethylation of FOXP3 promoter led to decrease in FOXP3 level in Treg cells. Inhibition of FOXP3 promoter hypermethylation promoted the secretion of IL-2, IL-10, and TGF-β1 in Treg cells.Conclusion: The number of Treg cells in CITP patients decreased, and the hypermethylation of FOXP3 promoter led to reduction of its expression in Treg cells, thus affecting the immune functioning of Treg cells.